Literature Review: Faktor Sanitasi Kapal dengan Keberadaan Vektor di Kapal - Rofiatul Asrifah; Novera Herdiani (Universitas Widya Gama Mahakam Samarinda, 2021)
Background: Ship are related to public health because they allow the spread of disease due to public health risk factors, one of which is the presence of vectors that can trigger disease exchange in human. The existence of vectors on board is caused by poor sanitation such as bad hygiene, inadequate lighting and ventilation, bad food storage, and scattered garbage that is not properly disposed of. Objectives: This literature review aims to determine the relationship between ship sanitation factors and the presence of vectors on ship Research Metodes: This study use the literature review method by searching for journals on the google scholar database and one search (2010-2020). The keyword used are